Royal mothers and their ruling children: wielding political authority from Antiquity to the early modern era - Woodacre, Elena; Fleiner, Carey (Queenship and power, 2015)
"This collection brings together a series of fascinating case studies of royal mothers ranging across time from Antiquity through to the seventeenth century, from the (in)famous -- Agrippina the Younger and Catherine de Medici -- to the lesser known -- Judith of Thuringia. This collection focuses on queens and elite women who were at the political heart of their respective realms and examines the often tense political dynamic between these royal mothers and their offspring. This volume describes a wide range of case studies to illustrate the volatile and sometimes controversial combination of motherhood, ambition, and political authority. These essays take a fresh look at the timeless issues of the 'woman behind the throne' and reveal how royal mothers could provide key support for their children both to gain and retain a throne through illuminating studies of both well-known royal mothers, such as Eleanor of Aquitaine, and Catherine de Medici, and less familiar figures including Juana Enríquez and the regents of the Khitan Liao in China"--